Kiai Leadership and Curriculum Innovation: A Study of the Curriculum Development of the Diniyah Program of Islamic Boarding Schools - Fadhil Ismail; Muhammad Rizky Mubarok; Imroatul Ma'rifah; Samsul Susilawati (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
The leadership of the kiai in Islamic boarding schools has a strategic role in the development of the madrasah diniyah curriculum. In this case, the kiai functions as the main decision maker for his leadership in planning the diniyah program curriculum that is integrated with formal education in the Islamic boarding school. This study aims to discuss the leadership of the kiai in the development of the diniyah program curriculum at the Tebuireng Jombang Islamic boarding school. This study uses a qualitative approach with a case study type. The data collection techniques use observation, interviews and documentation. The data analysis technique uses data reduction, data presentation, data validity and drawing conclusions. The results of this study indicate that KH. Abdul Hakim Mahfudz as a caregiver applies charismatic and transformational leadership that complement each other in developing the Islamic boarding school. Evidenced by the presence of components such as attributed charisma, idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration in his identity. The diniyah program curriculum is designed as a comprehensive guide for diniyah program learning that is integrated with the formal madrasah curriculum to support the formation of character and knowledge of students. The development orientation includes six aspects, namely program objectives, curriculum objects, learning processes, teacher roles, and learning environments. The leadership of the kiai in developing the diniyah program curriculum is as follows: 1.) Kiai as The Highest Strategic Decision Maker and Spiritual Enlightener 2.) Revitalization of the Islamic boarding school diniyah program.